2019
DOI: 10.3390/f10110978
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Tree Species Shape Soil Microbial Community via Regulating Assembly Processes in Planted Subtropical Forests

Abstract: Understanding the ecological processes that regulate microbial community assembly in different habitats is critical to predict microbial responses to anthropogenic disturbances and environmental changes. Rubber (Hevea brasiliensis) and Eucalypt (Eucalyptus urophylla) plantations (thereafter RP and EP) are rapidly established at the expense of forests in tropical China, greatly affecting tropical soils and their processes. However, the assembly processes of soil microbial communities after forest conversions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The present study also shows that SOC has a significant impact on the bacterial community structure in bulk soils. Our results show that AK and TK have a significant impact on bacterial community structure, especially in bulk soils, which is consistent with the results reported by Ma et al [ 24 ], who reported a statistical correlation between microbial structure and soil TK in Eucalyptus urophylla plantations. Leaching of K from the soil may explain this phenomenon [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study also shows that SOC has a significant impact on the bacterial community structure in bulk soils. Our results show that AK and TK have a significant impact on bacterial community structure, especially in bulk soils, which is consistent with the results reported by Ma et al [ 24 ], who reported a statistical correlation between microbial structure and soil TK in Eucalyptus urophylla plantations. Leaching of K from the soil may explain this phenomenon [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the lack of K not only directly affects the microbial communities but also indirectly limits the absorption and utilization of other nutrients by plants. In this sense, teak trees may facilitate the shift of bacterial communities towards a community with an increased ability to mobilize soil K [ 24 ]. Moreover, AP and TP were significantly correlated with bacterial community structure in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant trees provide various functions that guide overall forest community function and structure (Power et al, 1996). Observations suggest that dominant tree species direct the ecological processes that regulate microbial soil community assembly, which play a critical role in maintaining forest functional and structural stability (Ma et al, 2019). Dominant tree species are also driving factors in shaping spatial patterns of plant biodiversity, locally and regionally (Hao et al, 2007;Draper et al, 2019).…”
Section: Tree Speciesmentioning
confidence: 99%
“…Compared with primary forests, agricultural systems tend to have higher bacterial richness but lower fungal richness (Lan et al, 2017a;Cai et al, 2018;Tripathi et al, 2012;Kerfahi et al, 2016). Compared with Eucalyptus plantations, rubber plantations have been found to possess a higher diversity of both bacteria and fungi (Ma et al, 2019). Song et al (2019) reported that tropical forest conversion to rubber plantation results in reduced fungal microbial community network complexity.…”
Section: Introductionmentioning
confidence: 99%